Differential proteomic analysis of Clostridium perfringens ATCC13124; identification of dominant, surface and structure associated proteins - Sengupta Nabonita; Kumar Ravi; Bansod Sunita; Alam Syed; Singh Lokendra (BMC Microbiology, 2009)
Abstract Background Clostridium perfringens is a medically important clostridial pathogen causing diseases in man and animals. To invade, multiply and colonize tissues of the host, a pathogen must be able to evade host immune system, and obtain nutrients essential for growth. The factors involved in these complex processes are largely unknown and of crucial importance to understanding microbial pathogenesis. Many of the virulence determinants and putative vaccine candidates for bacterial pathogens are known to be surface localized. Results Using 2-DE mass spectrometry strategy, we identified major surface (22) and cell envelope (10) proteins from Clostridium perfringens ATCC13124 and those differentially expressed (11) in cells grown on cooked meat medium (CMM) in comparison with cells grown in reference state (tryptose-yeast extract-glucose medium). Riboflavin biosynthesis protein, ornithine carbamoyltransferase, cystathionine beta-lyase, and threonine dehydratase were the predominant proteins that exhibited 2.19 to 8.5 fold increase in the expression level in cells growing on CMM. Conclusion Ornithine carbamoyltransferase and cystathionine beta-lyase were over-expressed in cells grown on cooked meat medium and also identified in the surface protein fraction and the former was immunogenic; making them potential vaccine candidates. Based upon bioinformatic analysis; choloylglycine hydrolase family protein, cell wall-associated serine proteinase, and rhomboid family protein were predicted as surface protein markers for specific detection of C. perfringens from the environment and food. Most of the proteins over-expressed in CMM were shown to have putative function in metabolism, of which seven were involved in amino acid transport and metabolism or lipid metabolism.